If God still breathes, why can't I? Black Lives Matter and biblical authority - Parker, Angela N. 1971- (Grand Rapids, Michigan William B. Eerdmans Publishing Company, 2021)
Introduction: What is your relationship to the Bible? -- Stifled breathing : trained to be a white male biblical scholar -- White supremacist authoritarianism is not God's breath -- Stop gaslighting me -- Moving from stifled breath to full-throated faith -- Conclusion: Breathing womanist air.
"A challenge to the doctrine of biblical inerrancy and its role in propagating White supremacist authoritarianism in the Christian church"--
Includes bibliographical references and index
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Evidences, authority, etc; Authoritarianism -- Religious aspects -- Christianity; Black Lives Matter Movement -- Religious aspects -- Christianity; Racism -- Religious aspects -- Christianity; Womanist Theology; Race Relations -- Biblical teaching; White supremacy movements -- Religious aspects -- Christianity; United States -- Race relations